The Implementation of Islamic Education Management in the Development of Knowledge and Character at Higher Education Institutions - Sri Kadarsih; Kasful Anwar Us; Shalahudin (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study explores the implementation of Islamic education management at Al Mujaddid Sabak Institute, focusing on its role in developing students' knowledge and character. Using a qualitative approach with descriptive analysis, the research highlights the institution's holistic efforts, including curriculum development, professional teacher training, and innovative teaching methods. The findings reveal that the integration of Islamic values into the curriculum not only enhances academic outcomes but also shapes students' moral and ethical character. Despite challenges such as resource limitations and student resistance to active learning methods, the institution has addressed these through strategic leadership, collaboration with stakeholders, and continuous evaluation. The study concludes that effective Islamic education management significantly impacts the quality of graduates and their ability to contribute positively to society. This model provides valuable insights for other higher education institutions aiming to balance academic excellence with character development.